Differences in photodynamic therapy exposure time and Staphylococcus aureus counts - Adeline Jovita Tambayong; Ira Widjiastuti; Cecilia G. J. Lunardhi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: The success of endodontic treatment can be achieved when pathogenic bacteria are eliminated from the root canal and periapical tissue resulting in healing of such tissue. One of the bacteria located in root canals is Staphylococcus aureus (S. aureus) reportedly found to be in severe periapical abscesses. Photodynamic therapy is one current technology that can help eliminate microorganisms without causing damage to human body cells. Average of research has been conducted using different tools and bacteria to evaluate the effects of exposure time used in photodynamic therapy on the number of bacteria. Purpose: The research reported here aimed to determine the correlation between the exposure time of photodynamic therapy and the number of S. aureus bacteria. Methods: The S. aureus bacteria used in this research were divided into seven treatment groups: a control group and six treatment groups with respective exposure times of 10, 20, 30, 40, 50 and 60 seconds. All of the bacteria were administered a photosensitiser and radiated according to the treatment intended for each group. They were then planted in nutrient agar and incubated for 48 hours. The colonies of bacteria formed were calculated using the Quebec colony counter and subsequently analyzed by means of both Kruskal Wallis and Mann Whitney U tests. Results: After calculating the number of bacterial colonies, the average number of Staphylococcus aureus bacteria in the non-irradiated group was 119 CFU/ml, 29 CFU/ml in the group with a 10-second exposure time, 20 CFU/ml in the group with a 20-second exposure time, 13 CFU/ml in the group with a 30-second exposure time, 7 CFU/ml in the group with a 40-second exposure time, but none in the groups with exposure times of 50 or 60 seconds. Conclusion: The longer the photodynamic therapy exposure time, the greater the number of S. aureus bacteria eliminated. An exposure time of 50 seconds was found to be sufficient to exterminate all S. aureus bacteria present.